Peran Ilmu Nahwu-Sharf Terhadap Kemampuan Tafsir Peserta MTQ Cabang Tafsir Bahasa Indonesia - Mahfudhoh, Nailah; Yusuf, Kamal; Rohman, Abdur (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
The objectives of this study are to investigate how knowledge of Nahwu (Arabic syntax) and Sharf (Arabic morphology) helps participants of the Musabaqah Tilawatil Qur'an (MTQ) in the Indonesian Language Qur'anic Tafsir category strengthen their interpretation skills, as well as to identify the challenges participants face in mastering these two sciences for interpreting the Qur'an. This study takes a qualitative method, with 10 MTQ participants in the Indonesian Language Qur'anic Tafsir category and one of their trainers serving as a supportive informant. The data was gathered by observation, questionnaires, and in-depth interviews, then analyzed using interpretation techniques, thematic categorization, and data reduction. The results of the study reveal that the knowledge of Nahwu and Sharf considerably helps participants understand the structure of Qur'anic verses and interpret them more precisely, thereby improving their exegetical skills. However, while mastering the knowledge of Nahwu and Sharf, the participants face several problems, which undoubtedly produce diversity in their interpretation skills. These problems include the complexities of Nahwu and Sharf laws, a lack of preparation time, training methods, limited references, and distinctions in educational background and environment. The findings of this study can be used as a resource for MTQ participants in the Indonesian Language Qur'anic Tafsir category to improve their Qur'anic exegesis skills.